DIMETHOXYFLAVONE ISOLATED FROM THE STEM BARK OF STEREOSPERMUM KUNTHIANUM POSSESSES ANTIDIARRHOEAL ACTIVITY IN RODENTS - P., Ching F.; I.O, Otokiti; B., Egert-omoneukanrin (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
This study was undertaken to evaluate the antidiarrhoeal activity of 3, 7, 4/-trihydroxy-3/-(8//-acetoxy-7//-methyloctyl)-5, 6-dimethoxyflavone, a flavonoid isolated from the stem bark of Stereospermum kunthianum. The antidiarrhoeal activity was evaluated using rodent models with diarrhoea. The normal intestinal transit, castor oil-induced intestinal transit and castor oil-induced diarrhoea tests in mice as well as castor oil-induced intestinal fluid accumulation in rats were employed in the study. The animals were pretreated with distilled water (10 ml/kg for mice, 5 ml/kg for rats), dimethoxyflavone (25 mg/kg or 50 mg/kg), morphine (10 mg/kg), or indomethacin (10 mg/kg) before induction of diarrhoea with castor oil (0.2ml for mice and 2ml for rats). Dimethoxyflavone dose dependently and significantly reduced (P<0.05) castor oil-induced intestinal motility. Its antimotility effect at the dose of 50 mg/kg was higher compared to that of morphine (10 mg/kg). Dimethoxyflavone (25 mg/kg and 50 mg/kg) caused a delay in the onset of diarrhoea, reduction in the number and weight of wet stools and total stools in mice with castor oil-induced diarrhoea compared to the distilled water treated mice. Treatment with dimethoxyflavone (25 mg/kg or 50 mg/kg) did not produce any remarkable effect on castor oil-induced intestinal fluid accumulation in rats and normal intestinal transit in mice. The results indicate that dimethoxyflavone possesses antidiarrhoeal activity due to its intestinal antimotility effect and inhibition of other diarrhoeal pathophysiological processes. In conclusion, dimethoxyflavone reduced the frequency and severity of diarrhoea in the diarrhoeal models studied.